Peran Komunikasi Orang Tua Dalam Meningkatkan Kecerdasan Bahasa Anak Di RA Raiyatul Husnan Kec. Wringin Kab. Bondowoso - Nurhasanah (LP3M KH Yazid Karimullah Institute, 2024)
Children's language intelligence development is a crucial aspect of their growth, influenced by various factors. Parental communication plays a vital role in the formation and development of children's language abilities. This research aims to explore the role of parental communication in improving children's language intelligence and identify the most effective communication strategies. This research was conducted at RA Ra'iyatul Husnan Wringin Bondowoso. The approach used in this research is descriptive qualitative. Data collection techniques include interviews, observation, and documentation. The data analysis used is Miles and Huberman's data analysis. Based on the research that has been conducted, it can be concluded that parental communication increases children's language intelligence in RA Raiyatul Husnan District. Wringin District. Bondowoso is implemented through a series of strategies: Verbal Communication, Using varied Vocabulary, Reading Literacy and Discussion, Language Games and Emotional Support. The factors influencing children's language development at RA Ra'iyatul Husnan Wringin Bondowoso